Darriwilian (Middle Ordovician) δ13Ccarb chemostratigraphy in the Precordillera of Argentina: Documentation of the middle Darriwilian Isotope Carbon Excursion (MDICE) and its use for intercontinental correlation - Albanesi, Guillermo Luis; Bergström, Stig M.; Schmitz, Birger; Serra, Fernanda; Feltes, Nicolás Alexis; Voldman, Gustavo Gabriel; Ortega, Gladys del Carmen (Palaeogeography, Palaeoclimatology, Palaeoecology)
Although documented from Estonia, Latvia, Sweden, eastern North America, and China, the Middle Ordovician (Darriwilian) positive δ13C excursion known as the MDICE has previously not been recognized with certainty in South America. The most promising region in South America for detailed Middle Ordovician carbon isotope research is the Precordillera of western Argentina, where there are many excellent exposures of biostratigraphically well-dated carbonate successions spaning the Tremadocian through Sandbian stratigraphic interval. For this project, we collected numerous isotope and conodont samples from the middle Darriwilian Las Chacritas and Aguaditas formations at their type localities, which yielded important biostratigraphic data as well as informative δ13Ccarb values. In the E. pseudoplanus Zone in the upper half of the Las Chacritas Formation, there is a relatively modest but distinct δ13Ccarb excursion. Because its stratigraphic position and magnitude closely agree with the MDICE in other parts of the world, we recognize it as the first firm record of this excursion in South America. The fact that the δ13Ccarb curve from the Las Aguaditas Formation shows no such excursion is due to the existence of a stratigraphic gap between the Lower and Middle Members of this formation that cuts out the excursion interval. The Precordilleran MDICE is used for detailed long-range correlations with successions in Baltoscandia, Newfoundland, and China illustrating the usefulness of also this δ13Ccarb excursion as a global stratigraphic tool. A recent proposal of a greatly extended chronostratigraphic range of the Table Head Group on Newfoundland is rejected based on well-established biostratigraphic evidence. Fil: Albanesi, Guillermo Luis. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Museo de Paleontología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. ...